Bazhu Decoction, a Traditional Chinese Medical Formula, Ameliorates Cognitive Deficits in the 5xFAD Mouse Model of Alzheimer’s Disease - Peng, Axiang; Gao, Yuehong; Zhuang, Xiaomei; Lin, Yaoqi; He, Wencan; Wang, Yannan; Chen, Wenfan; Chen, Tingting; Huang, Xiaoqing; Yang, Renzhi; Huang, Yuanpeng; Xi, Shengyan; et al. (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD) is the most common neurodegenerative disease associated with aging. Currently, no effective drugs are available for AD patients. Bazhu Decoction (BZD), a traditional Chinese medicine formula, has been applied clinically to alleviate AD for many years and has good efficacy, but its mechanism is still unknown. This study evaluated the effect and further mechanism of BZD on ameliorating cognitive dysfunction in the 5xFAD transgenic mice model of AD. 40 three-month-old 5xFAD mice were randomly allocated to five groups: 5xFAD-Control, 5xFAD-BZD-L, 5xFAD-BZD-M, 5xFAD-BZD-H, and 5xFAD-Donep (n=8). 24 Wild-type littermates, used as control mice, were randomly divided into WT-Control, WT-BZD, and WT-Donep (n=8). The 5xFAD-Donep and WT-Donep mice were administered 20 mL/(kg·d) Donepezil HCL with a dosage of 0.65 mg/kg·d. The three 5xFAD-BZD and WT-BZD groups were administrated 20 mL/kg·d BZD with the dosage of 4.225, 8.450, 16.900, and 16.900 g/kg·d, respectively. All mice received treatment once daily by gavage for 12 weeks. Then behavioural tests were documented. Aβ plaques were detected by Immunohistochemistry. The MDA levels and SOD activity were detected by ELISA. The expression levels of APP, BACE1, and PS1 were documented by Western blot analysis. BZD had no effect on the locomotor activity of 5xFAD mice in open field test. The medium/high doses of BZD attenuated disinhibition behavioural alteration by increasing 5xFAD mice’s vigilance and attenuating behavioural disinhibition in the elevated plus maze, improved memory impairments in 5xFAD mice, as shown by an increase in the percentage of alternation triplet in the Y maze, and significantly ameliorated the impairment of spatial learning and memory in the Morris water maze. The medium and high doses of BZD decreased the deposition of Aβ plaques, and levels of BACE1 and PS1. And no effect on APP could be identified. The medium and high doses of BZD could also attenuate both MDA levels and SOD activity. BZD presents a positive effect on 5xFAD mice by decreasing APP processing and Aβ plaques and ameliorating oxidative damage. BZD may play a protective role in the cognitive and anxiety impairments and may be an interesting complementary therapeutic option for AD patients.